Factors Influencing Morbidity after Surgical Management of Malignant Thyroid Disease. (June 2013) - More, Yogesh; Shnayder, Yelizaveta; Girod, Douglas A.; Sykes, Kevin J.; Carlisle, Michael P.; Chalmers, Brian; Kraemer, CodyJo; Tsue, Terance T.
Objectives: We performed a retrospective study of cases from 2005 to 2010 at an academic tertiary care center to analyze the factors that influence morbidity in surgical management of thyroid malignancy. Methods: The rates of recurrent laryngeal nerve (RLN) injury and hypoparathyroidism (HPT) were analyzed in the entire cohort. The comparison groups were 1) primary surgery versus revision; 2) total thyroidectomy versus total thyroidectomy combined with neck node dissection; and 3) two groups defined by surgical technique according to the RLN approach: Group 1, in which the RLN was identified inferiorly in the tracheoesophageal groove, and group 2, in which the RLN was identified near the cricothyroid joint point of entry. Results: We reviewed 308 patients who underwent surgery for thyroid cancer. Thirty-six (11.7%) had temporary HPT, and 8 (2.6%) had permanent HPT. Of a total of 586 RLNs at risk, 16 (2.7%) had temporary damage and 2 (0.3%) had permanent damage. The incidences of temporary RLN injury significantly differed between the primary-surgery and revision-surgery groups (2.5% versus 15.6%; p = 0.001), and also between the groups with total thyroidectomy and thyroidectomy with neck dissection (1.2% versus 7.8%; p = 0.027). The incidences of temporary HPT were significantly different between the groups with primary surgery and revision surgery (6.6% versus 31.3%; p = 0.001), between the groups with total thyroidectomy and total thyroidectomy with neck dissection (4.7% versus 15.6%; p = 0.009), and between group 1 and group 2 (surgical technique in terms of RLN approach; 8.2% versus 17.9%; p = 0.011). Permanent HPT and permanent RLN injury both occurred rarely in this cohort, with no significant differences among comparison groups. Conclusions: Our study shows a higher incidence of temporary RLN injury and temporary HPT in revision surgery cases and in total thyroidectomy with neck dissection. Temporary HPT was significantly more common when the RLN was identified near the cricothyroid joint.